208k views
0 votes
Fill in the gaps in the equation below by

completing the square.
x² - 6x-1=(x −
|) ² − |

Fill in the gaps in the equation below by completing the square. x² - 6x-1=(x − |) ² − |-example-1

1 Answer

5 votes

Answer:

(x -3)² -10

Explanation:

You want the vertex form of x² -6x -1, found by completing the square.

Completing the square

The square of a binomial is ...

(x -a)² = x² -2ax +a²

The constant in this perfect square trinomial is the square of half the coefficient of the linear term: a² = (-2a/2)²

Application

To complete the square for the given quadratic, the perfect square trinomial must have a constant of (-6/2)² = 9. We can add and subtract 9 to rearrange the quadratic to the desired form.

x² -6x -1

= (x² -6x +9) -1 -9 . . . . . . . +9 -9 was added

= (x -3)² -10

User Jan Johansen
by
5.9k points